B13 Huntington's disease phenotypes and disrupted corticostriatal connectivity observed in a novel ipsc-derived in vitro co-culture model. (September 2018) - Casey, Caroline S; Qiu, Yichen; Bentham, Matthew P; Smith, Edward J; Lignani, Gabriele; Andre, Ralph; Wood-Kaczmar, Alison; Tabrizi, Sarah
Abstract : Background: The corticostriatal (CS) pathway, comprising layer V cortical projection neurons (CPN) and medium spiny neurons (MSN), is one of the first brain pathways to succumb to Huntington's disease (HD) pathology. As a result, disrupted CS connectivity is evident and contributes to the motor and cognitive symptoms experienced by HD patients. Aims: The aim of this work is to investigate the CS pathway using a purely human tissue-derived in vitro system. Methods: This project utilizes two familial iPSC lines; the control line, with 20/20 HTT CAG repeat lengths (20Q), and a juvenile HD line, with 20/73 CAG repeats (73Q). These lines were differentiated in parallel to either MSNs or CPNs, and co-cultured in microfluidic chambers to physically recapitulate the human CS pathway. Results: High-resolution fluorescence microscopy has revealed the formation of CS synapses within MFC co-cultures, complimented by live cell imaging with calcium binding dye Fluo4, which demonstrates the successful transmission of calcium between neuronal populations within MFCs. CPN cultures show a HD phenotype in their cytoskeletal dynamics, as axon projection efficiency is drastically reduced in 73Q CPNs compared to 20Q. Furthermore, 73Q MSNs exhibit enhanced cell death after BDNF-withdrawal compared to 20Q cultures. Finally, the intrinsic membrane properties of iPSC-derived MSNs also differ with disease state, as 73Q MSNs are hyper-excitable, with an extended latency to fire and extended refractory period. Conclusion: These results provide a novel insight into the human CS pathway and suggest subtle differences in both the development and function of the CS pathway in HD.